Effect of finish line design and cement space thickness on the marginal accuracy of monolithic zirconia crowns - Eldamaty, Mohamed; Abdel-Aziz, Mohammed; El-Kouedi, Ahmed; Hamza, Tamer (Brazilian Dental Science, 2020)
Objective: The purpose of this study was to evaluate the effect of finish line design and cement space thickness on the marginal accuracy of monolithic zirconia crowns. Materials and methods: Thirty crowns were fabricated from translucent zirconia (inCoris TZI) using Cerec in-Lab system and divided into three main groups (10 each) according to the finish line type of the die (knife-edge, chamfer, and shoulder). Every group was divided into two subgroups (5 each) according to cement space thickness (20 and50?m). Optical impressions were taken for the dies using the Cerec scanner and cement space was set twice for every finish line design; 20 and 50 ?m. The completed crowns were cemented to the dies and the marginal gap was evaluated. The collected data was statistically analyzed using Mann-Whitney U test and Kruskal-Wallis test and the significance level was set at P ? 0.05. Results: Regarding the marginal gap; there was no statistically significant difference between different finish line designs or between different cement space thicknesses. Conclusion: Neither finish line design nor cement space thickness has an effect on the marginal gap of inCoris TZI crowns. Keywords Cement space; Finish line; Marginal fit; Monolithic zirconia.